The Impact of Russia-Ukraine War on Bangladesh’s Economy: A Supply Chain Perspective and Way Forward - Saleheen, Ferdoush; Habib, Md. Mamun; Nazmuzzaman Hye, Mohammad; Bvepfepfe, Benjamin (ExcelingTech, 2024)
Bangladesh’s economy is facing significant challenges restricting from the Russia-Ukraine conflict, intensified by its status as an oil-importing nation vulnerable to global oil price fluctuations. This study addresses the current perspectives and challenges which include inflationary pressures, trade imbalances, and disruptions in the supply chain, leading to increased expenditures for essential commodities. This research was developed through a systematic literature review based on secondary data, including online databases, journals, and review papers, etc. This exploratory study reveals that policymakers need to diversify energy sources, forge new trade partnerships, and implement measures to bolster economic resilience. The economic fallout from the conflict, surpassing the actual war in cost, has depleted the central bank's reserves, prompting austerity measures. The forex market experiences volatility, contributing to high trade deficits and the highest inflation rate in recent years. Bangladesh must address forex management challenges and formulate prudent policies for economic recovery. The conflict has disrupted global commodity markets, leading to inflationary pressures and increased costs for businesses in Bangladesh, especially larger organizations handling rising raw material costs and weak consumer demand. The rationale of this paper is to evaluate the literature on this aspect and apprehend the global demand, and supply of food and commodities, economic impacts in Bangladesh, challenges in global trade, trade relations, currency fluctuations, inflation, emergency price, and its consequences, recognize gaps and advocate future research itineraries. The paper offers a synopsis and appraisal of the overall economy of Bangladesh and finally navigates a way forward to the policymakers which would unlock further research to develop this sector.